Something, someday - Gorman, Amanda, 1998- (Viking, 2023)
"Presidential inaugural poet and #1 New York Times bestselling author Amanda Gorman and Caldecott Honor and Coretta Scott King Honor winner Christian Robinson have created a timeless message of hope. Sometimes the world feels broken. And problems seem too big to fix. But somehow, we all have the power to make a difference. With a little faith, and maybe the help of a friend, together we can find beauty and create change. With intimate and inspiring text and powerfully stunning illustrations, Something, Someday reveals how even the smallest gesture can have a lasting impact" --